2017
DOI: 10.3389/fnbeh.2017.00129
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Averageness in Faces Does Not Generalize to Non-Human Primates

Abstract: Facial attractiveness is a long-standing topic of active study in both neuroscience and social science, motivated by its positive social consequences. Over the past few decades, it has been established that averageness is a major factor influencing judgments of facial attractiveness in humans. Non-human primates share similar social behaviors as well as neural mechanisms related to face processing with humans. However, it is unknown whether monkeys, like humans, also find particular faces attractive and, if so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…43 As Neelam A Vashi stated, beautiful faces are more prototypical of, more representative of, and better examples of, a population of faces. 44 Although some investigations held that faces accompany with special features would be rated more magnetic than the average face, and some emphasized that the average face likely plays a role in face recognition rather than in judgments of facial attractiveness, 45 a growing number of researches have proved that resemble to a facial prototype is prerequisite to be attractive. 46 Furthermore, it has been reported that inclination of averageness is a cross-cultural neurobehavioral response.…”
Section: Discussionmentioning
confidence: 99%
“…43 As Neelam A Vashi stated, beautiful faces are more prototypical of, more representative of, and better examples of, a population of faces. 44 Although some investigations held that faces accompany with special features would be rated more magnetic than the average face, and some emphasized that the average face likely plays a role in face recognition rather than in judgments of facial attractiveness, 45 a growing number of researches have proved that resemble to a facial prototype is prerequisite to be attractive. 46 Furthermore, it has been reported that inclination of averageness is a cross-cultural neurobehavioral response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, initial sensory biases could evolve as signals of mate quality (Garcia & Ramirez, 2005; Rhodes, 2006), or mechanisms derived from mate choice could operate on top of perceptual biases to make humans particularly attentive to facial attractiveness in conspecifics (Little & Jones, 2003). These possibilities seem, at first glance, to conflict with reports showing that components of attractiveness such as symmetry or prototypicality can influence preferences for a variety of stimuli, including those both relevant and not relevant to mate choice in humans (Halberstadt & Rhodes, 2000, 2003; Reber, Schwarz, & Winkielman, 2004) and monkeys (Anderson, Kuwahata, Kuroshima, Leighty, & Fujita, 2005; Damon, Méary, et al, 2017; Waitt & Little, 2006, but see Tomeo, Ungerleider, & Liu, 2017). However, the influence of these components has been shown to be modulated by the category of stimuli presented.…”
mentioning
confidence: 94%
“…Previous studies have mainly focused on the effects of global facial shape (e.g. averageness 6 13 , symmetry 7 , 9 , and sexually dimorphic shape cues 14 ) and expression 15 , 16 while some others have examined the effects of facial skin colour 17 – 27 (for review, see Thornhill and Gangestad, 1999 1 and Little et al, 2011 2 ).…”
Section: Introductionmentioning
confidence: 99%